Head and Neck Pain in Patients Presenting with Acute Aortic Dissection - Philip, Stephen; Missov, Emil; Gilon, Dan; Hutchison, Stuart; Khoynezhad, Ali; Evangelista, Arturo; Bonaca, Mark; Conklin, Lori; Appoo, Jehangir; Di Eusanio, Marco; Braverman, Alan; Forteza, Alberto; Montgomery, Daniel; Nienaber, Christoph; Isselbacher, Eric; Eagle, Kim (AORTA, 2018)
Background Head and neck pain is an atypical presentation of acute aortic dissection. Classic teaching associates this pain with proximal dissections, but this has not been extensively studied.Methods Patients enrolled in the International Registry of Acute Aortic Dissection from January 1996 to March 2015 were included in this study. We analyzed the demographics, presentation, treatment, and outcomes of Type A aortic dissection patients presenting with head and neck pain (n = 812, 25.8%) and compared it with those without these symptoms (n = 2,341, 74.2%).Results Patients with head and neck pain were more likely to be white, female, with a family history of aortic disease. Patients with head and neck pain had higher percentages of back pain (43.3% vs. 37.5%, p = 0.005) and chest pain (87.6% vs. 79.3%, p < 0.001). On imaging, a higher percentage of those with head and neck pain had arch vessel involvement (44.3% vs. 38%, p = 0.010) and intramural hematoma (11.7% vs. 8.1%, p = 0.003). Surgical management was more common in patients with head and neck pain (89.8% vs. 85.2%, p = 0.001). Regarding outcomes, patients with head and neck pain had significantly higher rates of stroke than those without head and neck pain (13% vs. 9.9%, p = 0.016); however, overall mortality was lower for those with head and neck pain (19.5% vs. 23%, p = 0.038). Those with head and neck pain only had higher overall mortality compared to those with head and neck pain with chest or back pain (34.6% vs. 19.9%, p = 0.013). A logistic regression of mortality revealed that preoperative hypotension and age > 65 years were significantly associated with increased mortality.Conclusion Presence of head and neck pain in Type A dissection is associated with more arch involvement, intramural hematoma, and stroke. When isolating those with head and neck pain only, there appear to be a higher rate of comorbidity burden and higher overall mortality.
Keywords: Head Pain; neck pain; aortic dissection